2013
DOI: 10.1111/1467-8551.12015
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization Strategies ofEuropeanUnion Electric Utilities

Abstract: As part of the debate about globalization and regionalization, this paper adds a perspective that has so far remained underexposed, that of (formerly state-owned) firms in (previously) regulated industries, in order to better understand the (changing) role of the home country/region in internationalization processes in the context of regional market liberalization. This paper explores the global/regional orientations of the seven major EU electric utilities from five different home countries, which are active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 59 publications
(123 reference statements)
4
33
0
1
Order By: Relevance
“…Recent articles in the field of international business have shed more light on multinationals' climate-related resource commitments, both conceptually (Kolk and Pinkse, 2008;Pinkse and Kolk, 2012) and empirically, related to foreign direct investment in renewables (Hanni et al, 2011;Kolk et al, 2013;UNCTAD, 2010). Government policies have been important, and they have taken various forms, ranging from provision of public subsidies, knowledge and infrastructure, to market creation and regulation, including protection of intellectual property rights, investment facilitation and/or promotion, and international (green) development assistance.…”
Section: Country-specific Factors Relevant To International Businessmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent articles in the field of international business have shed more light on multinationals' climate-related resource commitments, both conceptually (Kolk and Pinkse, 2008;Pinkse and Kolk, 2012) and empirically, related to foreign direct investment in renewables (Hanni et al, 2011;Kolk et al, 2013;UNCTAD, 2010). Government policies have been important, and they have taken various forms, ranging from provision of public subsidies, knowledge and infrastructure, to market creation and regulation, including protection of intellectual property rights, investment facilitation and/or promotion, and international (green) development assistance.…”
Section: Country-specific Factors Relevant To International Businessmentioning
confidence: 99%
“…Considering the state of renewable foreign direct investment (activities that seem most relevant to climate change issues), it can be concluded that even though least-developed countries have hardly been involved, the past decade has seen a considerable growth in both energy generation and equipment manufacturing projects, with developed-country utilities as leading investors (Hanni et al, 2011;Kolk et al, 2013;UNCTAD, 2010). In terms of Table 1, data show that companies from the first category are most important for renewable-energy generation investments, also due to competitive advantage built up via their European home-country contexts, and saturated domestic markets, reflecting a specific combination of the three factors identified in this article (sector, company and country peculiarities).…”
Section: Some Implications and Suggestionsmentioning
confidence: 99%
“…Energy sector reforms are significant to sustainable energy development and involve reviewing and reforming subsidies, establishing credible regulatory frameworks, developing policy environments through regulatory interventions, and creating market-based approaches such as emissions trading (IPCC, 2013). Kolk et al (2014) investigate the regional directions of the seven major European Union electric utilities from five different home countries, which are vigorous in both fossil-fuel and generation of renewable energy. The study advocate discrete regionalization patterns for business units and diverse firm-specific benefits, with strategic opportunities related to asset positions.…”
Section: Resultsmentioning
confidence: 99%
“…The same research methodology challenge was recently shared by Kolk et al (2013) in the same industry context as they stated "extracting exact figures on (firm) presence in specific markets has been challenging due to the paucity of information in firms' annual reports …the restructuring of companies or business units and availability of (disclosed) activity." However, the combination of different types of information from different sources made it possible to identify key development steps for each of the case companies.…”
Section: Research Design and Case Companiesmentioning
confidence: 99%
“…However, research focusing on the international activity of electricity power producers is limited (Kolk, 2013), specifically those that have targeted emerging markets. Additionally it has been recognized that empirical research is lacking on related strategies, i.e.…”
Section: Introductionmentioning
confidence: 99%